Surface tension of flotation solution and its influence on the selectivity of the separation between apatite and gangue minerals. - Martins, B. K. (Minerals & Metallurgical Processing : An International Peer-Reviewed Journal)
This work presents and discusses the influence of the surface tension of methanol/water mixtures on the flotation response of apatite versus gangue minerals conditioned with flotation reagents (75 g/t cornstarch and 100 g/t berol 867)at pH 10.6. Berol 867 is a collector composed of sodium alkyl sarcosinate plus nonionic surfactant. The highest schulz efficiency of separation (recovery of apatite minus recovery of gangue) was achieved at =51.0mN/m. The critical surface tension of wettability of apatite was found to occur at 34.7 mN/m when determined by means of gamma flotation experiments, and it was 33.9 mN/m when determined by Zisman's approach.